(untitled) (International Journal of Physiology, 2019)
Background The common macrovascular complications of diabetes are heart disease and stroke, which accounts for about 50% of death in diabetic patients.1, 2 Diabetes mellitus (DM) is a common secondary cause of hyperlipidemia, particularly, if glycaemic control is poor. 3 Non-high-density lipoprotein-cholesterol (non-HDL-C) is a better measure of cardiovascular disease prediction in contrast with glycosylated hemoglobin (HbA1c) in type 2 diabetic patients. Objectives In the present study, the correlation of non-HDL-C with HbA1c were examined and evaluated in patients with type 2 diabetes mellitus. Materials and Method A total of 50 type 2 diabetics were included in the study with a mean age of 55.78(SD: 13.77)years of both gender previously diagnosed regardless of their sociodemographic characteristics and were invited for the assessment of lipid profile and HbA1c levels in Infilife healthcare private limited of Bengaluru city. Results Mean (SD) Hba1c levels and Non-HDL levels were 7.60% (2.01) & 159.32(95.60) mg/dL respectively. The study revealed a significant correlation between Hba1c levels and Non-HDL levels with a correlation coefficient(r) of 0.29[p<0.05]. Conclusion The present study showed that non-HDL-C positively correlates with HbA1c indicating better predictor of glycemic control among Type 2 Diabetes